Volatile compounds and lactic acid bacteria in spontaneous fermented sourdough - Kam .W.Y; Wan Aida .W.M; Sahilah .A.M; Maskat .M.Y (Universiti Kebangsaan Malaysia, 2011)
The aim of this study is to identify the predominating lactic acid bacteria (LAB) in a spontaneous fermented wheat sourdough. At the same time, an investigation towards volatile compounds that were produced was also carried out. Lactobacillus plantarum has been identified as the dominant species of lactobacilli with characters of a facultative heterofermentative strain. The generated volatile compounds that were produced during spontaneous fermentation were isolated by solvent extraction method, analysed by gas chromatography (GC), and identified by mass spectrophotometer (MS). Butyric acid has been found to be the main volatile compound with relative abundance of 6.75% and acetic acid at relative abundance of 3.60%. Esters that were formed at relatively low amount were butyl formate (1.23%) and cis 3 hexenyl propionate (0.05%). Butanol was also found at low amount with relative abundance of 0.60%. The carbohydrate metabolism of Lactobacillus plantarum may contributed to the production of acetic acid in this study via further catabolism activity on lactic acid that was produced. However, butyric acid was not the major product via fermentation by LAB but mostly carried out by the genus Clostridium via carbohydrate metabolism which needs further investigation